EFL Teachers’ Problems and Solutions in Teaching English to Students with Intellectual and Developmental Disability - Utami, Revita Putri; Suharyadi, Suharyadi; Astuti, Utari Praba (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Sekolah Luar Biasa (SLB) is a school specialized for students with special needs, particularly students with Intellectual and Developmental Disability (IDD). In Indonesia, the government guarantees that they have the same right to study formally and informally; and to get the best teachers in the teaching and learning process. In English language teaching, however, even qualified teachers have problems while teaching English to students with IDD. Despite the urgency to solve the problems faced by teachers who teach English or a foreign language to special needs students, especially IDD, there are only a few articles covering this topic. This study, which uses a descriptive qualitative method, aims at uncovering the problems and solutions of five English teachers in teaching students with IDD in SLB Pembina Tingkat Nasional Bagian C Malang. In order to obtain the needed data, an observation checklist, a field note, and an interview guide were utilized. The findings revealed that problems faced by the teachers were related to teachers’ English proficiency, methods and media used in teaching, and students’ ability in learning. The teachers used different solutions to overcome the problems, but the most common solution was using repetition in teaching and practicing. This solution was used as the students had difficulties in understanding and remembering the lesson. The other solutions used during the teaching and learning process include YouTube videos, English learning application, posters, and BSE.